A multi-centre randomised trial to compare the effectiveness of geriatrician-led admission avoidance hospital at home versus inpatient admission. - Shepperd, S; Cradduck-Bamford, A; Butler, C; Ellis, G; Godfrey, M; Gray, A; Hemsley, A; Khanna, P; Langhorne, P; McCaffrey, P; Mirza, L; Pushpangadan, M; et al. (BioMed Central, 2017)
Background There is concern that existing models of acute hospital care will become unworkable as the health service admits an increasing number of frail older people with complex health needs, and that there is inadequate evidence to guide the planning of acute hospital level services. We aim to evaluate whether geriatrician-led admission avoidance to hospital at home is an effective alternative to hospital admission. Methods/Design We are conducting a multi-site randomised open trial of geriatrician-led admission avoidance hospital at home, compared with admission to hospital. We are recruiting older people with markers of frailty or prior dependence who have been referred to admission avoidance hospital at home for an acute medical event. This includes patients presenting with delirium, functional decline, dependence, falls, immobility or a background of dementia presenting with physical disease. Participants are randomised using a computerised random number generator to geriatrician-led admission avoidance hospital at home or a control group of inpatient admission in a 2:1 ratio in favour of the intervention. The primary endpoint ‘living at home’ (the inverse of death or living in a residential care setting) is measured at 6 months follow-up, and we also collect data on this outcome at 12 months. Secondary outcomes include the incidence of delirium, mortality, new long-term residential care, cognitive impairment, activities of daily living, quality of life and quality-adjusted survival, length of stay, readmission or transfer to hospital. We will conduct a parallel economic evaluation, and a process evaluation that includes an interview study to explore the experiences of patients and carers. Discussion Health systems around the world are examining how to provide acute hospital-level care to older adults in greater numbers with a fixed or shrinking hospital resource. This trial is the first large multi-site randomised trial of geriatrician-led admission avoidance hospital at home, and will provide evidence on alternative models of healthcare for older people who require hospital admission.